A Maternal High-Fat Diet Induces DNA Methylation Changes That Contribute to Glucose Intolerance in Offspring - Zhang, Qian; Xiao, Xinhua; Zheng, Jia; Li, Ming; Yu, Miao; Ping, Fan; Wang, Tong; Wang, Xiaojing (Frontiers in Endocrinology, 2019)
Scope: Overnutrition in utero is a critical contributor to the susceptibility of diabetes by programming, although the exact mechanism is not clear. In this paper, we aimed to study the long-term effect of a maternal high-fat (HF) diet on offspring through epigenetic modifications. Procedures: Five-week-old female C57BL6/J mice were fed a HF diet or control diet for 4 weeks before mating and throughout gestation and lactation. At postnatal week 3, pups continued to consume a HF or switched to a control diet for 5 weeks, resulting in four groups of offspring differing by their maternal and postweaning diets. Results: The maternal HF diet combined with the offspring HF diet caused hyperglycemia and insulin resistance in male pups. Even after changing to the control diet, male pups exposed to the maternal HF diet still exhibited hyperglycemia and glucose intolerance. The livers of pups exposed to a maternal HF diet had a hypermethylated insulin receptor substrate 2 (Irs2) gene and a hypomethylated mitogen-activated protein kinase kinase 4 (Map2k4) gene. Correspondingly, the expression of the Irs2 gene decreased and that of Map2k4 increased in pups exposed to a maternal HF diet. Conclusion: Maternal overnutrition programs long-term epigenetic modifications, namely, Irs2 and Map2k4 gene methylation in the offspring liver, which in turn predisposes the offspring to diabetes later in life.